Analisis Analisis sistem informasi akuntansi pada pemakaian bahan baku guna meningkatkan efektivitas pengendalian intern persediaan PT Gelflex Indonesia - Vincensia selvin des ratnasari ndraha, Vincensia selvin des ratnasari ndraha (SCIENTIA JOURNAL, 2022)
This study aims to analyze the accounting information system on the use of raw materials in increasing the effectiveness of PT Gelflex Indonesia's internal inventory control whether it has been implemented properly or not. Accounting information systems are very useful for companies, not only in controlling the use of raw materials, accounting information systems will also facilitate the company's operational activities. Qualitative method is the method applied in this research by using interview and observation data collection techniques and literature review. The results of this study indicate that the implementation of the accounting information system at PT Gelflex Indonesia has been running properly, it can be seen from the division of the organizational structure, but there are still errors made by the production department, in which the employee or leader incorrectly enters the number of inputs in the system, resulting in mismatch of the actual amount that is still available with the amount that has been inputted into the system. From the results of the research, the researchers suggest that further research needs to be carried out with supervision and training regarding the importance of implementing an accounting information system that is in accordance with applicable standards for employees in order to support the continuity of the company's production and business continuity in the future.